Augmenting glycosylation‐directed folding pathways enhances the fidelity of HIV Env immunogen production in plants. Issue 10 (19th July 2022) - Margolin, Emmanuel; Allen, Joel D.; Verbeek, Matthew; Chapman, Ros; Meyers, Ann; van Diepen, Michiel; Ximba, Phindile; Motlou, Thopisang; Moore, Penny L.; Woodward, Jeremy; Strasser, Richard; Crispin, Max; et al.
Abstract: Heterologous glycoprotein production relies on host glycosylation‐dependent folding. When the biosynthetic machinery differs from the usual expression host, there is scope to remodel the assembly pathway to enhance glycoprotein production. Here we explore the integration of chaperone coexpression with glyco‐engineering to improve the production of a model HIV‐1 envelope antigen. Calreticulin was coexpressed to support protein folding together with Leishmania major STT3D oligosaccharyltransferase, to improve glycan occupancy, RNA interference to suppress the formation of truncated glycans, and Nicotiana benthamiana plants lacking α1, 3‐fucosyltransferase and β1, 2‐xylosyltransferase was used as an expression host to prevent plant‐specific complex N ‐glycans forming. This approach reduced the formation of undesired aggregates, which predominated in the absence of glyco‐engineering. The resulting antigen also exhibited increased glycan occupancy, albeit to a slightly lower level than the equivalent mammalian cell‐produced protein. The antigen was decorated almost exclusively with oligomannose glycans, which were less processed compared with the mammalian protein. Immunized rabbits developed comparable immune responses to the plant‐produced and mammalian cell‐derived antigens, including the induction of autologous neutralizing antibodies when the proteins were used to boost DNA and modified vaccinia Ankara virus‐vectored vaccines. This study demonstrates that engineering glycosylation‐directed folding offers a promising route to enhance the production of complex viral glycoproteins in plants.